THE ROLE OF EMOTIONAL INTELLIGENCE IN MODERN EDUCATION: BRIDGING PSYCHOLOGY AND PEDAGOGY (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores how emotional intelligence (EI) functions as a vital bridge between psychology and pedagogy. It argues that emotional development is inseparable from cognitive growth and that the cultivation of EI within classrooms leads to stronger motivation, healthier relationships, and higher academic performance. Drawing on psychological theories, neuroscientific findings, and selected case studies, the paper proposes practical strategies for integrating EI into teacher training and curriculum design.